Sistema híbrido de eletrólise e microfiltração para o tratamento de água de maças - Carpes, Vanessa Maria (2017)
The industries of the productive chain of apples (packing house) use high potable water flows into the gutters for transporting and cleaning, which is continually contaminated with fungi and organic matter, changing the color and turbidity too. The filtration system traditionally used at water treatment is not capable of increasing his life cycle in the process of apples processing industry, being necessary water discarding. Therefore, the implementation of an efficient water treatment system during the industrial process, provides a reduction in the uptake and release flows, minimizing environmental impacts and costs. Electrolysis, among the physico-chemical, presents advantages when compared to conventional treatments. Nevertheless, this treatment alone has limitations on the formation of aggregates in the form of microparticles, making it difficult to separate them by traditional processes. That sense the highlights are the membrane separation processes, because they are physical systems that separate easily flakes formed in electrolysis. Based on the above, this study aims to extend the life cycle of water in the industries apples processing with the application of electrolysis hybrid system / microfiltration. T he methodology comprises the development of a hybrid system of electrolysis and membranes, through the electrolytic treatment application electrocoagulation with carbon steel cathode electrode and an aluminum anode in a batch process (Stage 1) and continuous (Stage 2), then separation process microfiltration membrane (MSP) (Stage 3) and electrolytic treatment electrooxidation (OE) (Stage 4), carbon steel cathode and anode electrode ruthenium oxide. The best condition for the removal of pollutants from Organic Matter (OM), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), turbidity, color and fungi obtained in Stage 1 were hydraulic detention time (HDT) = 40 minutes, system agitation = 40 rpm, current density (CD) = 20 A/m2, pH 8,00 and temperature of 10 °C, which allowed for the development of Stage 2. In Stage 3, the tests performed on the combined Continuous Electrolytic Reactor (CER) and MSP presented mean MO removals of 54%, COD of 72%, SST 83%, turbidity and color of 92%, and fungi 100%, at both pressures. The combination CER + MSP + OE improved the removal efficiency of these pollutants. The combination of the CER + MSP + OE hybrid system proved to be a promising alternative for extending the water life cycle in the apples processing industry.